God must be crazy II : this time, everybody's going crazier [video recording]. (Quezon City : Magna Vision, 2004)
This delightful sequel to hilarious hit comedy is a piece of divinely inspired lunacy! N!xau recreates his starring role as Xixo the Bushmanm who lives deep in the African desert, following the same way of life his ancestors have for thousands of years.
Keywords: Gods -- Drama; African people -- Drama